2017
DOI: 10.3390/ijms18020397
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in Interstitial Cells: Focus on Telocytes

Abstract: In this review, we describe the current knowledge on calcium signaling pathways in interstitial cells with a special focus on interstitial cells of Cajal (ICCs), interstitial Cajal-like cells (ICLCs), and telocytes. In detail, we present the generation of Ca2+ oscillations, the inositol triphosphate (IP3)/Ca2+ signaling pathway and modulation exerted by cytokines and vasoactive agents on calcium signaling in interstitial cells. We discuss the physiology and alterations of calcium signaling in interstitial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 156 publications
1
16
0
Order By: Relevance
“…Although a lot of studies are needed to talk about a certain function of TCs, a possible contribution to the mechanisms of carcinogenesis is not negligible, by the modification of the tumor microenvironment. As our team previously showed, TCs are not pacemakers but modulate the activity of the surrounding cells using calcium signaling [73]. Our results showed that uterine TCs express T-type calcium channels that might play a role in the generation of endogenous bioelectric signals responsible for the regulation of the surrounding cell behavior [74,75].…”
Section: Human Breast Telocytessupporting
confidence: 50%
“…Although a lot of studies are needed to talk about a certain function of TCs, a possible contribution to the mechanisms of carcinogenesis is not negligible, by the modification of the tumor microenvironment. As our team previously showed, TCs are not pacemakers but modulate the activity of the surrounding cells using calcium signaling [73]. Our results showed that uterine TCs express T-type calcium channels that might play a role in the generation of endogenous bioelectric signals responsible for the regulation of the surrounding cell behavior [74,75].…”
Section: Human Breast Telocytessupporting
confidence: 50%
“…TCs have been localized in several other organs as well . Several investigations have suggested that TCs and PDGFRα‐positive cells influence the intestinal motility, among many other functions …”
Section: Introductionmentioning
confidence: 99%
“…17 Several investigations have suggested that TCs and PDGFRα-positive cells influence the intestinal motility, among many other functions. 12,[18][19][20][21] Electron microscopic studies showed that both ICCs and fibroblast-like cells were present around the myenteric ganglia of the human small and large intestine. 5,9 Double immunofluorescence, combined with confocal microscopy, proved that CD34immunoreactive, fibroblast-like cells were distinct but closely attached to ICCs both in human and mouse stomach, small intestine and colon.…”
mentioning
confidence: 99%
“…In mammals, this interaction is responsible for creating a 3D network between clusters of telocytes (Radu et al, ) the same way as has been observed in the interstitial compartment of the fishes. In mammals, such contact may be homocellular (between telocytes) or heterocellular (between a telocyte and other cell types, for example, telocyte‐immune cell interaction, telocyte‐neuron, telocyte‐blood vessels; Radu et al, ). This is another indication that the interstitial cell observed in this study is a telocyte.…”
Section: Discussionmentioning
confidence: 71%
“…A final aspect to be considered is the presence of calcium in these interstitial cells, supposedly the telocytes, in fishes. Radu et al () describe a possible role played by the signaling of calcium in the telocytes in uterine physiology and reproductive system of mammals.…”
Section: Discussionmentioning
confidence: 99%